An impact evaluation of technology adoption by smallholders in Sichuan, China: The case of sweet potato-pig systems - Lapar, Ma. Lucila; Nguyen Ngoc Toan; Chengyi Zou; Jinyuan Liu; Xianglin Li; Randolph, Thomas F. (International Livestock Research Institute, 2011)
We employ propensity score matching (PSM) framework to examine the impact of sweet potatobased feed technology adoption on household-based pig production in Sichuan, China. An ex post survey in six villages was conducted in 2009, of which five villages were in project intervention sites (exposed area) and one village in the same township but not exposed to project intervention (nonexposed area). We randomly selected 111 households in the exposed areas from the list of households previously interviewed in a baseline survey and 53 households from non-exposed area. Matching estimators such as nearest neighbor matching (NNM), radius matching (RM) and kernel matching (KM) were used to estimate average treatment effects. Results indicate positive net benefit from adoption of sweet potato-based feeding technology, i.e., gross margin estimates of silage adopters are on average higher by 2-4 RMB per kg liveweight of output than non-adopters of similar characteristics. Silage adopters are also likely to produce 3-7 more slaughter pigs per year than non-adopters having similar characteristics, on average. Analysis of factors driving adoption indicates that sweet potato-based feed technology is not suitable in all smallholder context in Sichuan. Where this is suitable is in systems where sweet potato is an important crop, where there is limited access to input markets such as in upland or mountainous areas, where corn is not an important crop, and where households raise no more than 10 pigs given available household labor for pig raising in rural areas (generally either old people who are no longer active in the labor force, or young children who are still in school). Overall, the results show that sweet potato-based feed technology plays an important role in helping household-based pig producers become resilient, by having options in feeding strategies that help them cope with volatility in output prices (e.g., prices of live pigs as a function of retail prices of pork) and input prices (e.g., price of corn vis-à-vis price of pork, price of industrial feed). Exposure to the technology and its benefits through actual demonstration also appears to be more effective in engendering uptake and sustaining adoption.